Re-imagining decent work for home care workers in Australia. (2nd October 2017) - Charlesworth, Sara; Malone, Jenny
ABSTRACT: The progress in Australia towards the full industrial recognition of home care work as 'work' has stalled. This paper draws on International Labour Organization (ILO) Convention 189 on Decent Work for Domestic Workers 2011 to argue for a re-imaging of decent minimum standards for home care workers in Australia. While to date Australia has not ratified ILO 189, home care workers, who are employed to work in the homes of the aged or with people with disabilities, fall within the scope of this Convention. Drawing on the scholarship and activism that has emerged around ILO 189 we argue that with the slow but steady shift to more fragmented, individualised and informal employment relationships in home care services re-imagining employment protections for home care workers in Australia is crucial. Recasting minimum labour standards for work described as both 'work like all other' and 'work like no other work' could well provide a basis for a more substantial re-imagining of Australian employment regulation for all workers.